Positive Solutions of Eigenvalue Problems for a Class of Fractional Differential Equations with Derivatives - Xinguang Zhang; Lishan Liu; Benchawan Wiwatanapataphee; Yonghong Wu (Abstract and Applied Analysis)
By establishing a maximal principle and constructing upper and lower solutions, the existence of positive solutions for the eigenvalue problem of a class of fractional differential equations is discussed. Some sufficient conditions for the existence of positive solutions are established.